Rapport du Comité de résidents du Jeffery Hale : Année 2021-2022 - Cloutier, Robert (Jeffery Hale - Saint Brigid's (JHSB), 2022)
Au cours de 2021-2022, le Comité de résidents du Jeffery Hale a tenu dix séances de travail via Zoom compte tenu des exigences sanitaires Covid-19. Ce mode de fonctionnement a permis aux membres du Comité de maintenir le lien d’appartenance et de réaliser des projets d’amélioration de la qualité de vie des résidents et leurs proches.

Understanding the Long-term Care Experience of Official Language Minorities in Canada: An Environmental Scan - Hsu, Amy T.; Ménard, Alixe; Scott, Mary (2022)
Members of minority and racialized communities across Canada commonly experience disparities in health and healthcare. In the context of the COVID-19 pandemic, minority and racialized individuals have been found to report poorer health outcomes and added barriers to healthcare access. While there is growing understanding of the impact of COVID-19 on individuals who live and work in residential long-term care (LTC) homes and other congregate care settings, little attention has been directed at examining inequities in the care experience and care-related outcomes that equity-seeking groups, including Official Language Minority Communities (OLMC), face within LTC. It’s clear that there is a need for systemic change within LTC; the pandemic, especially in its first two waves, highlighted several pre-existing issues within this sector. To ensure high-quality and equitable care for all aging Canadians, these system-level changes must be informed by evidence.
Keywords: Official Language Minority Community (OLMC)

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Dre. Amy T; Ménard, Alixe; Scott, Mary (2022)
Les membres des communautés racisées et en situation minoritaire du Canada vivent souvent des disparités en matière de santé et de soins de santé. Dans le contexte de la pandémie de COVID-19, on a constaté que les personnes membres d’une minorité et les personnes racisées signalaient de moins bons résultats de santé et des barrières supplémentaires à l’accès aux soins de santé. Bien que l’on comprenne de plus en plus l’incidence de la COVID-19 sur les personnes vivant et travaillant dans des établissements de soins de longue durée (SLD) et dans d’autres établissements de soins collectifs, on a porté peu d’attention à l’examen des inégalités dans l’expérience des soins et des résultats liés aux soins auxquels font face les groupes en quête d’équité, y compris les communautés de langue officielle en situation minoritaire (CLOSM). Il est clair qu’il faut apporter des changements systémiques au sein du secteur des SLD; la pandémie, surtout au cours de ses deux premières vagues, a mis en lumière plusieurs problèmes préexistants dans ce secteur. Pour assurer des soins de grande qualité et équitables pour tous les Canadien(ne)s âgés, ces changements au niveau du système doivent être fondés sur des données probantes.
Keywords: Official Language Minority Community (OLMC)

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)

World Elder Abuse Awareness Day : Well-Treatment in All Circumstances - Michaud, Julie (2021)

Comité des usagers JHSB : Mandat 2018-2021 - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Composition du Comité des usagers du Jeffery Hale - Saint Brigid's - Jeffery Hale - Saint Brigid's (JHSB) (2020)

[Jeffery Hale Residents' Committee List / Jeffery Hale comité des résidents liste de membres] - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Saint Brigid's Residents' Committee / Saint Brigid's comité des résidents - Jeffery Hale - Saint Brigid's (JHSB) (2020)

2019-2020 Annual Report : Saint Brigid's Home Residents' Committee - Leger, Valerie (Jeffery Hale - Saint Brigids (JHSB), 2020)
The roles and responsibilities of our Residents’ Committee (shared with the Users’ Committee) are to: 1. Inform users of their rights and obligations. 2. Help improve the quality of living conditions and evaluate the degree of satisfaction with the services at the institution. 3. Defend the collective rights and interests of users or, upon request, the rights and interests of an individual user, before the institution or any competent authority. The SBH Residents’ Committee is overseen by the JHSB Users’ Committee. As president, I therefore attended its meetings to receive and give information of interest to SBH. As committees we strive to work closely with administrators at SBH to ensure our concerns translate into quality services for residents.

Rapport du Comité des résidents du Jeffery Hale : Année 2019-2020 - Cloutier, Robert (Jeffery Hale - Saint Brigid's (JHSB), 2020)
Au cours de l’année 2019-2020, le Comité des résidents du Jeff s’est rencontré à sept reprises. Les rencontres se sont tenues principalement au 2e étage du Jeff le troisième vendredi du mois. Étant donné la venue du Coronavirus le Comité a tenu sa dernière séance le 21 février 2020. Par ailleurs, des communications téléphoniques et par courriel ont lieu régulièrement avec les membres. Le Comité est composé de résidents, de proches aidants et d’ex proches aidants. Pour que tous les membres s’impliquent dans les travaux du Comité et que les séances de travail soient plus productiv

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report : 2019-2020] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2020)
The Jeffery Hale – Saint Brigid’s Users’ Committee met nine times from April 2019 to February 2020 in addition to its Annual Meeting on May 8, 2019. The Annual Meeting was held in conjunction with an Information Meeting by the Administration for Saint Brigid’s Residents and families and was well attended. The March 2020 meeting was cancelled because of the Covid19 virus pandemic. Throughout the year the Committee’s meetings were held in the Saint Brigid’s Boardroom because of renovations to the Jeffery Hale Pavilion.

Adapting Services During the Pandemic : The Example of Jeffery Hale-Saint Brigid's and Its Partners - Duchesne, Anne (2020)

Bienvenue au Jeffery Hale votre résidence, votre milieu de vie : Guide d’accueil des résidents et de leurs proches - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Welcome to Saint Brigid’s Home Residential and Long Term Care Center : Welcome Guide for Residents and their Loved Ones - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Access to Public Long-term Care : Useful information for seniors and their loved ones - Jeffery Hale Community Services (2017)

Saint Brigid's Residents' Committee : Welcome to Your Home! / Saint Brigid's Comité des résidents : Bienvenu(e) chez vous ! - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Composition du comité consultatif du Jeffery Hale – Saint Brigid’s: Mandat 3 ans : 2015-2018 - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Programme des soins palliatifs et de fin de vie - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Action prévention : La sécurité est notre responsabilité à tous - Haberlin, John (2015)
Number of Pages: 4

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)
Number of pages: 8

Comité des résidants Jeffery Hale : Nous vous souhaitons la bievenue chez-vous - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Consultation publique sur les conditions de vie des aînes : Un enjeu de société, une responsabilité qui nous interpelle tous - Conseil catholique d'expression anglaise (2007)
Le Conseil catholique d’expression anglaise aimerait féliciter le gouvernement du Québec pour avoir reconnu l’importance des problèmes affectant les aînés et notre population vieillissante et pour avoir créé le poste de ministre responsable des Aînés. Nous accueillons avec plaisir l’initiative de Mme Marguerite Blais, ministre responsable des Aînés, de tenir des audiences publiques sur les conditions de vie des aînés au Québec. Cet enjeu constitue une grande source de préoccupations pour notre communauté et pour ses institutions au service des personnes âgées, dont l’expérience dans ce domaine est considérable.

Choices through Knowledge: Community training in palliative care - Jones, Jo-Ann; Quebec Association for Adult Learning (QAAL) (2004)

Users and Residents : Have Your Say / Usagers et résidents : La parole est à vous - Jeffery Hale – Saint Brigid’s (JHSB) Users' Committee

Comité de résidents Saint Brigid’s Residents’ Committee : Bienvenue chez vous ! Welcome to Your Home! - Jeffrey Hale - Saint Brigid's (JHSB)

Executive Summary : The English Speaking Catholic Council’s Response to Public Consultation on Seniors’ Living Conditions - The English Speaking Catholic Council (ESCC)
For the English Speaking Catholic Council (ESCC), the care of seniors, especially the frail elderly, is a moral and social imperative for us all. Our community has created a number of specialized institutions and services over the past one hundred and fifty years that allow us to carry out our responsibilities to seniors, but Quebec faces many challenges if we want to protect and promote fully the interests of older citizens.